Cultivar cotidianamente resistencias y autonomías emancipatorias será necesario para tejernos entre pueblos - Vilma Almendra; Vicente Romero; Arauco Chihuailaf (Les Cahiers ALHIM)
Vilma Almendra inherited the fighting spirit from her mother. She has a university training and she contributed to the collective appropriation of the Technologies of Information and Communication. She also tells the improvements and difficulties met by the North Cauca’s Indigenous movement.